PENGARUH BUDAYA ORGANISASI DALAM PENGEMBANGAN MANFAAT TMMD DI PROVINSI SUMATERA BARAT - Aldri Frinaldi; Alahan Sinaga; Bobi Rizki Ananda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
A good organizational culture can have a positive influence on the implementation of the TMMD program in the District, increase collaboration and coordination between team members, increase creativity and innovation, increase accountability and transparency, and increase public trust and participation. Therefore, government agencies and the community need to continue to encourage good organizational culture in implementing the TMMD program in the District. The influence of public organizational culture on the TMMD program can have a very important impact in improving the quality, effectiveness and efficiency of programs as well as providing great benefits to the community. Therefore, government agencies and the community need to continue to encourage good organizational culture and provide support for programs that can provide benefits to society. A successful and transparent TMMD program can increase public trust in the government and program implementing agencies. Improving the image of program implementing agencies. TMMD programs that provide great benefits to the community can improve the image of program implementing agencies in the public eye.